Factors Affecting the Intention to Buy Halal Food by the Millennial Generation: The Mediating Role of Attitude - Lilis Mega Setiawati; Chairy Chairy; Jhanghiz Syahrivar (Universitas Pelita Harapan, 2019)
The increasing Muslim population in recent years has resulted in an increased demand for halal food. This study aims to determine the effect of religiosity, awareness of halal food, and attitude towards halal food on purchase intention by millennial generations. This research is quantitative research with survey analysis method. The data used in this study is primary data using a questionnaire as a research instrument. The researchers surveyed 230 Muslim respondents of millennial age at President University. The sampling technique used in this study is judgment sampling method. Data analysis was performed using Partial Least Square-Structural Equation Model (PLS-SEM) software, namely SmartPLS version 3.2.8. The hypotheses were tested through path coefficient, t-Significance, p-Value, and determination coefficient (R²). Based on the results of this study, it is found that: 1) halal awareness has a significant effect on attitude towards halal food, 2) religiosity, halal awareness and attitude towards halal food each has a significant effect on purchase intention of halal food and finally, 3) halal awareness as mediated by attitude towards halal food has an effect on purchase intention of halal food. Whereas the relationship between religiosity and attitude towards halal food and the relationship between religiosity and purchase intention of halal food as mediated by attitude towards halal food cannot be supported. The result of this research is useful to predict the future of the halal industry in Muslim-majority countries. It is recommended that food marketers should consider these elements when producing and preparing marketing campaigns for halal foods.Bahasa Indonesia Abstrak: Meningkatnya populasi Muslim akhir-akhir ini berakibat pada meningkatnya permintaan terhadap makanan halal. Studi ini dimaksudkan untuk mengetahui pengaruh religiositas, kesadaran terhadap makanan halal, dan sikap terhadap makanan halal, terhadap intensi membeli makanan halal di kalangan generasi milenial. Penelitian ini merupakan penelitian kuantitatif yang menggunakan metode survai. Data yang digunakan merupakan data primer yang diperoleh dengan menggunakan kuesioner sebagai instrumen penelitian. Sampel penelitian adalah 230 orang Muslim dari generasi milenial di President University. Teknik sampling yang digunakan adalah judgment sampling method. Analisis data dilakukan dengan menggunakan Partial Least Square-Structural Equation Model (PLS-SEM) software, yaitu SmartPLS version 3.2.8. Hipotesa penelitian diuji dengan melihat nilai koefisien jalur, nilai t, nilai p, dan koefisien determinsasi (R²). Berdasarkan hasil analisis data, ditemukan bahwa: 1) kesadaran halal mempengaruhi sikap terhadap makanan halal secara signifikan, 2) religiositas, kesadaran halal, dan sikap terhadap makanan halal, masing-masing memiliki pengaruh yang signifikan terhadap intensi membeli makanan halal, 3) sikap terhadap makanan halal memediasi pengaruh kesadaran halal terhadap intensi membeli makanan halal. Hasil penelitian juga memperlihatkan bahwa pengaruh religiositas atas sikap terhadap makanan halal tidak didukung data, demikian pula sikap terhadap makanan halal tidak memediasi pengaruh religiositas terhadap intensi membeli makanan halal. Hasil penelitian ini diharapkan bermanfaat untuk memperkirakan masa depan industri Halal di negara yang berpenduduk mayoritas Muslim. Para pemasar makanan perlu mempertimbangkan variabel yang digunakan dalam penelitian ini ketika menghasilkan dan mempersiapkan kampanye pemasaran untuk makanan halal.